2014
DOI: 10.1039/c4ta02378a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of ZnCo2O4nanowire cluster arrays on Ni foam for high-performance asymmetric supercapacitors

Abstract: ZnCo2O4 NWCAs on Ni foam as electrodes for high-performance asymmetric supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(74 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…Significant TMOs suffer from their poor electrical conductivities, resulting in limited capacitance performances. Recent works have shown that ternary spinel oxides such as NiCo 2 O 4 and ZnCo 2 O 4 can exhibit better electrochemical performances than single-component metal oxides owing to their synergistic effect to improve electron conductivities and provide more active sites for redox reaction [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Significant TMOs suffer from their poor electrical conductivities, resulting in limited capacitance performances. Recent works have shown that ternary spinel oxides such as NiCo 2 O 4 and ZnCo 2 O 4 can exhibit better electrochemical performances than single-component metal oxides owing to their synergistic effect to improve electron conductivities and provide more active sites for redox reaction [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among the mentioned ternary oxides, ZnCo 2 O 4 has attracted much interest and attention because of its better electrochemical activity and it exhibit higher conductivity. Furthermore, ZnCo 2 O 4 is well known having low cost, abundant resources and for its environmental friendliness [17].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, nickel cobaltite (NiCo 2 O 4 ) and zinc cobaltite (ZnCo 2 O 4 ) are the most studied compositions because of their higher electrochemical activity, low cost, abundant resources and environmental friendliness when compared with monometallic counterparts such as nickel oxide or cobalt oxide. [18][19] Moreover, the potential window for NiCo 2 O 4 is only 0.4-0.6V, 17 which hardly finds practical applications. Kumbhar and coworkers reported spinel CoFe 2 O 4 thin film prepared by using chemical bath deposition which demonstrated specific capacitance of 366 Fg -1 at a constant and high potential window of 1.0 V. 9,17 Particularly, among the spinel metal ferrites (MFe 2 O 4 ) system, ZnFe 2 O 4 is promising due to its low toxicity, high specific surface area, highly electroactive nature, good chemical and thermal stability, environmental benignity, low cost and rich abundance on Earth.…”
Section: Introductionmentioning
confidence: 99%